Functional and genetic analysis of choroid plexus development in zebrafish - Henson, Hannah E.; Parupalli, Chaithanyarani; Ju, Bensheng; Taylor, Michael R. (Frontiers in Neuroscience, 2014)
The choroid plexus, an epithelial-based structure localized in the brain ventricle, is the major component of the blood-cerebrospinal fluid barrier. The choroid plexus produces the cerebrospinal fluid and regulates the components of the cerebrospinal fluid. Abnormal choroid plexus function is associated with neurodegenerative diseases, tumor formation in the choroid plexus epithelium, and hydrocephaly. In this study, we used zebrafish (Danio rerio) as a model system to understand the genetic components of choroid plexus development. We generated an enhancer trap line, Et(cp:EGFP)sj2, that expresses enhanced green fluorescent protein (EGFP) in the choroid plexus epithelium. Using immunohistochemistry and fluorescent tracers, we demonstrated that the zebrafish choroid plexus possesses brain barrier properties such as tight junctions and transporter activity. Thus, we have established zebrafish as a functionally relevant model to study choroid plexus development. Using an unbiased approach, we performed a forward genetic dissection of the choroid plexus to identify genes essential for its formation and function. Using Et(cp:EGFP)sj2, we isolated 10 recessive mutant lines with choroid plexus abnormalities, which were grouped into five classes based on GFP intensity, epithelial localization, and overall choroid plexus morphology. We also mapped the mutation for two mutant lines to chromosomes 4 and 21, respectively. The mutants generated in this study can be used to elucidate specific genes and signaling pathways essential for choroid plexus development, function, and/or maintenance and will provide important insights into how these genetic mutations contribute to disease.